'A cry in the dark': a qualitative exploration of living with cluster headache. Issue 4 (November 2021) - Andre, Laura; Cavers, Debbie
Context: Cluster headache is a rare primary headache disorder said to be one of the most painful conditions in existence. Limited evidence demonstrates cluster headache patients have difficulties securing a diagnosis and poor access to services. There is a gap in research around psychosocial needs, meaning there are no evidence-based guidelines to inform optimal management of this patient group in primary care. Objectives: The aim of this study is to explore the perspectives of cluster headache patients in the United Kingdom in order to suggest ways their care can be improved. Methods: It is an in-depth qualitative study involving telephone interviews with 15 participants with either chronic or episodic cluster headache. Semi-structured interviews (43–58 minutes) were conducted, recorded and transcribed verbatim. Two researchers conducted thematic analysis to identify themes. Results: Participants described the impact cluster headache has on their quality of life. They also felt the legitimacy of their disorder was questioned. This situation was often exacerbated by a reported lack of awareness among General Practitioners (GPs), which negatively impacted their care in terms of diagnosis and access to treatments and specialists. They attempted to control the pain through treatments and avoiding triggers, often with detrimental consequences for their social contact and mental health. Conclusion: Findings indicate the need to improve the lived experience of cluster headache patients in two key areas: (1) raising awareness of the disorder and its impact among GPs, and (2) extending care beyond clinical treatment provision, supporting patients in self-management and addressing its psychosocial impact, with implications for the management of this group in primary care.